Analysis of Behavioral Factors in the Use of Traditional Medicine: Observational Study in Yogyakarta, Indonesia - Adi Nugrahanti, Maria Cyrilla Iglesia; Yosef Wijoyo; Yustina Sri Hartini; Nunung Priyatni (Eureka Herba Indonesia, 2024)
Traditional medicine has long been used by the people of Yogyakarta, Indonesia as an alternative treatment to modern medicine. Various factors influence traditional medicine use, including psychological factors such as attitudes, subjective norms, and perceived behavioral control. This research aims to determine the factors that influence the use of traditional medicine among the people of Yogyakarta Indonesia using the theory of planned behavior (TPB). This research was conducted using an analytical observational research design with a cross-sectional design. Data was collected from 110 respondents living in Yogyakarta who met the inclusion and exclusion criteria. The research instrument is a questionnaire that refers to the TPB construct which has been tested for validity and reliability. Data analysis was carried out using logistic regression statistical tests and Pearson correlation tests. The results of the analysis show that attitudinal factors and perceived behavioral control partially contribute to the intention to use traditional medicine, while the subjective norm construct does not contribute. Attitudes and perceived behavioral control are important factors that influence the intention to use traditional medicine among Indonesian people. This suggests that interventions that focus on increasing positive attitudes and perceived behavioral control can increase the use of traditional medicine.